2015
DOI: 10.1042/cs20140672
|View full text |Cite
|
Sign up to set email alerts
|

Activated regulatory T-cells attenuate myocardial ischaemia/reperfusion injury through a CD39-dependent mechanism

Abstract: Regulatory T-cells (Tregs) are generally regarded as key immunomodulators that maintain immune tolerance and counteract tissue damage in a variety of immune-mediated disorders. However, its role in myocardial ischaemia/reperfusion injury (MIRI) remains unknown. The purpose of the present study was to determine whether Tregs exert a beneficial effect on mouse MIRI. We examined the role of Tregs in murine MIRI by depletion using 'depletion of regulatory T-cell' (DEREG) mice and adoptive transfer using Forkhead b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 56 publications
2
51
0
Order By: Relevance
“…We first observed that activated Treg cells appear in response to MIRI, consistent with previous reports that Treg cells are detected in heart tissue with MIRI [32]. In addition, we observed a rapid infiltration of Tregs in heart draining lymph nodes, beginning at 3 days and peaking at 7 days post-reperfusion, suggesting specific recruitment of Tregs from the peripheral blood to the infarct, and from the heart to immune organs, which is driven by MIRI.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We first observed that activated Treg cells appear in response to MIRI, consistent with previous reports that Treg cells are detected in heart tissue with MIRI [32]. In addition, we observed a rapid infiltration of Tregs in heart draining lymph nodes, beginning at 3 days and peaking at 7 days post-reperfusion, suggesting specific recruitment of Tregs from the peripheral blood to the infarct, and from the heart to immune organs, which is driven by MIRI.…”
Section: Discussionsupporting
confidence: 79%
“…The majority of previous experimental studies on post-MI healing have demonstrated that Tregs play a protective role in this process [13, 19, 32, 45]. However, Mathes et al found that endogenous and MHC-II non-restricted Foxp3+ T-cells could drive MIRI [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of CD39 on Tregs in limiting tissue injury has been studied in myocardial infarction (MI) [74]. Elevated levels of CD39 can be observed in Treg populations in MI patients after primary percutaneous coronary intervention (PCI).…”
Section: Functional Molecules Expressed or Produced By ‘Repair’ Tregsmentioning
confidence: 99%